Regulatory Frameworks for Crypto Assets: Comparative Fiqh Study Between Malaysia and Indonesia - Mohamad Amerzan Mohamad Sobri; Muneer Ali Abdul Rab (USIM Press, 2025)
The purpose of this study is to examine the regulatory frameworks governing cryptocurrencies in Malaysia and Indonesia through the lens of Islamic law (Shariah), this study sought to address the growing need for clarity regarding the compatibility between these digital assets and the principles of Shariah. With technological advancements rapidly changing the way financial transactions are conducted; it became imperative to assess how governments have adapted their regulatory approaches to accommodate the emergence of crypto assets and to ensure the use of crypto assets align with shariah principle. Utilizing a descriptive qualitative research design, this study provided an in-depth examination of the challenges associated with developing the guideline for Shariah compliant crypto assets while also exploring potential solutions for aligning their usage with the principles of Islamic finance. By integrating theoretical and practical perspectives, this investigation shed light upon the complex issues involved in regulating crypto assets under Shariah, ultimately contributing valuable insights towards improving existing policies governing digital assets particularly in the context of Malaysia.